Diagnostic Value of lncRNA FGD5-AS1 Sponge miR-223-3p in Infantile Pneumonia and Its Prognostic Effect on Rehabilitation - Ren, Hong-Ping; Wen, Hong-Lin; Liu, Ya-Nan; Cai, Lin (Journal of Pediatric Infectious Diseases, 2024)
Objective This study aimed to uncover the value of long noncoding RNA FGD5-AS1 (lncRNA FGD5-AS1) in the diagnosis of infantile pneumonia and explore its pathological mechanism in lung fibroblasts. This research may provide a potential biomarker for diagnosing patients and predicting their rehabilitation outcomes.Methods This study included 92 children with infantile pneumonia as the research object, and an equal number of healthy children were introduced as controls. The FGD5-AS1 content was detected using real-time quantitative polymerase chain reaction (RT-qPCR) assay. The diagnostic value of FGD5-AS1 was evaluated by receiver operating characteristic (ROC) and logistic analysis. The molecular mechanism of FGD5-AS1 and miR-223-3p was studied by luciferase activity assays. The impact of abnormal FGD5-AS1 expression on the proliferation and apoptosis of lung fibroblasts was analyzed using the cell counting kit-8 (CCK-8) and flow cytometry.Results FGD5-AS1 expression was decreased in the serum of infantile pneumonia patients, which may be a diagnostic marker for children with pneumonia. Furthermore, FGD5-AS1 has the ability to predict patient outcomes. FGD5-AS1 levels in lung fibroblasts (WI-38) decreased when induced by lipopolysaccharide (LPS). This decline resulted in reduced cell proliferation ability, increased apoptosis rate, and elevated inflammatory factor content. However, upregulated FGD5-AS1 counteracted the effects of LPS on WI-38 cells activity and inflammatory factors.Conclusion FGD5-AS1 may act as a potential marker in infantile pneumonia, and regulate the biological activity and inflammation level of lung fibroblasts by targeting miR-223-3p.
Keywords: infantile pneumonia; FGD5-AS1; miR-223-3p; lung fibroblast; diagnosis